2021
DOI: 10.3390/plants10030591
|View full text |Cite
|
Sign up to set email alerts
|

The Toxic Effects of Antibiotics on Freshwater and Marine Photosynthetic Microorganisms: State of the Art

Abstract: Antibiotic residues have been commonly detected worldwide in freshwater, estuarine, and marine ecosystems. The review summarizes the up-to-date information about the toxic effects of over 60 antibiotics on nontarget autotrophic microorganisms with a particular focus on marine microalgae. A comprehensive overview of the available reports led to the identification of significant knowledge gaps. The data on just one species of freshwater green algae (Raphidocelis subcapitata) constitute 60% of the total informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 80 publications
0
17
0
Order By: Relevance
“…However, the application of FLO has increased interest in its toxic and side effects including hematopoietic toxicity, immunotoxicity, genetic toxicity, and embryonic toxicity in animals ( Guan et al, 2011 ; Hu et al, 2014 ; Ren et al, 2017 ; Hu et al, 2020 ). Moreover, terrestrial and aquatic plants could take FLO up from the polluted environment and display marked mitonuclear protein imbalances and toxic effects ( Zhang et al, 2020 ; Sharma et al, 2021 ). Previous studies indicate that FLO contaminants in the environment can enter the human body through the food chain and water, which leads to a disturbance of the microbiome in pregnant women and childhood obesity ( Wang et al, 2017 ; Zhou et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the application of FLO has increased interest in its toxic and side effects including hematopoietic toxicity, immunotoxicity, genetic toxicity, and embryonic toxicity in animals ( Guan et al, 2011 ; Hu et al, 2014 ; Ren et al, 2017 ; Hu et al, 2020 ). Moreover, terrestrial and aquatic plants could take FLO up from the polluted environment and display marked mitonuclear protein imbalances and toxic effects ( Zhang et al, 2020 ; Sharma et al, 2021 ). Previous studies indicate that FLO contaminants in the environment can enter the human body through the food chain and water, which leads to a disturbance of the microbiome in pregnant women and childhood obesity ( Wang et al, 2017 ; Zhou et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, photosynthesis was a more sensitive parameter for the macrolide, ERY probably due to its mode of action and it would likely be a reliable endpoint for antibiotics designed to target bacterial protein synthesis and/or DNA replication. Majority of the toxicity studies using algae are 3 -4 days exposures [13] and chronic studies (≥7 days exposure) investigating the molecular pathways or mechanisms of toxic effects of antibiotics on microalgae should be carried out as this is not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…The green algae used in this study belong to a diverse group of aquatic photosynthesizing microscopic organisms called phytoplankton [13]. The aquatic food web is sustained by the energy obtained by phytoplankton through photosynthesis [14].…”
Section: Introductionmentioning
confidence: 99%
“…2017) Due to similarities between bacteria and green microalgae's chloroplast and mitochondria, in uencing microalgae chloroplast by protein synthesis inhibitor antibiotics seems reasonable. Chloroplast is also the place of synthesis carbon-xing enzymes and photosynthesis proteins so any harm to chloroplast results in photosynthesis reduction or inhibition (Sharma et al 2021) (Chen et al 2020). Furthermore DNA gyrases are exist in eukaryotes and are employed as targets of quinolons in chloroplast and mitochondria (Yang and Liu 2020).…”
Section: Sulfonamidesmentioning
confidence: 99%
“…Comparing data con rm the toxicity of tetracyclines on both fresh and marine species microalgae.Macrolides: The results of present study suggest that inhibition effect of TYL is relates to the concentration of the macrolide, whereas 1mg/L of TYL increased the algal growth, the 0.5 and 0.25 mg/L reduced it. On the other hand the comparative experiment assessed the TYL effect on fresh and marine microalgae and evaluated IC 50 0.27 and 0.99 mg/L for marine diatoms; Cylindrotheca closterium and Navicula ramosissima, respectively (Hagenbuch and Pinckney 2012 which are higher than evaluated parameters than fresh water species with 4days IC 50 values; 74.3, 35 and 4.3 mg/L for C. vulgaris, D. subspicatus and R. subspicatus, whereas 1 day IC 50 value 0.0089 mg/L was reported for P. subcapitata(Sharma et al 2021) that seems the toxicant gets more effective over time.Toxic effect of the other macrolide: ERY on green microalgae species have been evident previously by using S. capricornutum, C. vulgaris, Chlamydomonas reinhardtii and Ankestrodesmus falcatus, 0.35-12 mg/L of ERY inhibited 50% of the algal growth (Miazek and Brozek-Pluska 2019) the similar observation supports not only the toxicant effect of 0.3 mg/L ERY on S. capricornutum but also the reduction in the chlorophyll contents by increasing order of the macrolide concentration(Liu et al 2011). More complete study demonstrated e ciency of ERY on transporting electron and photosystem I and II in cyanobacteria(Sharma et al 2021) that explain the inhibitory mechanism of ERY on microalgae.…”
mentioning
confidence: 94%